2006
DOI: 10.1063/1.2385214
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence spectra of Eu-doped GaN with various Eu concentrations

Abstract: Variation of the luminescence spectra of Eu-doped GaN with varying Eu concentration ranging from 0.6to8.0at.% was investigated. Eu-related luminescence originating from the D05-F27 transition of Eu3+ was observed at about 622nm. The luminescence basically consisted of three peaks. The relative intensity of the three peaks changed remarkably at the Eu concentration of around 2.0–3.5at.% which corresponds to a structural phase transition from a single crystalline to a polycrystalline structure. This indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Among the RE elements, Er is more interesting since the Er ions can produce both visible light at 558 nm (green, one of the primary colors) and IR light at 1.54 mm whose spectrum region coincides with the principal low-loss window in the absorption spectrum of aluminosilicate optical fibre. Since, Favennec et al [2] reported that the thermal quenching effect in RE-doped semiconductors decreases with increasing bandgap of the host crystal material, the wide gap semiconductors, such as GaN, have recently received much attention [3][4][5][6][7]. Despite extensive studies, however, the exact nature of the active luminescent centers and the radiation mechanism of Er-doped GaN are still not clear yet.…”
Section: Introductionmentioning
confidence: 97%
“…Among the RE elements, Er is more interesting since the Er ions can produce both visible light at 558 nm (green, one of the primary colors) and IR light at 1.54 mm whose spectrum region coincides with the principal low-loss window in the absorption spectrum of aluminosilicate optical fibre. Since, Favennec et al [2] reported that the thermal quenching effect in RE-doped semiconductors decreases with increasing bandgap of the host crystal material, the wide gap semiconductors, such as GaN, have recently received much attention [3][4][5][6][7]. Despite extensive studies, however, the exact nature of the active luminescent centers and the radiation mechanism of Er-doped GaN are still not clear yet.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore wide gap semiconductor such as GaN has received much attention. [5][6][7][8] However, another barrier called concentration quenching effect 9,10 hinders the developments. The concentration quenching effect means that the RErelated emission intensity increases with RE-concentration up to a certain concentration, and then decreases remarkably.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] In PL measurement, excitation source is photon, for device application however, electron excitation such as cathodoluminescence ͑CL͒ is more useful than photon excitation. However research reports on the optical properties of Er-doped GaN using CL are not so many as PL.…”
mentioning
confidence: 99%
“…4(d). For hexagonal-GaN:Eu, PL spectrum due to the 5 D 0 -7 F 2 transitions of Eu 3+ ions is split into three lines [8], corresponding to three PL peaks (α), (β) and (γ). For GaN:Eu, generally, a PL peak at 619 nm (ζ) was not observed.…”
Section: Resultsmentioning
confidence: 99%